Bilateral or multilateral?: International financial flows and the dirty-work hypothesis - Dreher, Axel; Lang, Valentin; Rosendorff, B. Peter; Vreeland, James Raymond (The journal of politics, 2022)
How do governments choose between bilateral and multilateral foreign policy? We argue that powerful governments can exploit their influence over multilateral organizations to hide domestically contentious foreign policies. Applying this argument to international financial flows, we formulate hypotheses on the choice between bilateral and multilateral financing for political purposes. We test them by examining how the United States incentivizes support for decisions on UN Security Council resolutions. Introducing a new data set on 2,530 Security Council decisions between 1946 and 2015, the results show that temporary Security Council members receive more bilateral and multilateral financing only when they support the positions of the United States. The United States uses bilateral aid to incentivize the support of allies and uses its power over the World Bank and the International Monetary Fund to channel multilateral finance to less friendly countries.
Gesehen am 22.08.2024